CONTROL COMMAND SYSTEMS IMPACT ON THE RAILWAY OPERATIONAL SAFETY - Pawlik, Marek (Science and Transport Progress, 2015)
Purpose. Safety is seen as a must, for railway transport market. However it is not so obvious what does safety exactly mean as it means different things for different experts. Showing safety ensured by control command systems as a component of the railway operational safety and pointing associated challenges especially those arising from subdivision of the national railway system into different entities. Methodology. To achieve this purpose control command and signalling systems keeping safe distances between trains, preventing setting conflicting train routs, locking of the mobile elements of the switches, protecting the level crossings, enabling safe incorporation of additional trains were analyzed. Findings. Article analyses how control command system influence operational safety taking into account safety of the control-command system itself, interfaces on one side between signalling systems and control command system and on the other side between control command system and vehicle control systems, transmission, maintenance, and operation in degraded modes of running. Originality. New and high-effective scope of tests which are necessary for putting new control command installation into service both track-side and on-board are proposed. Practical value. Control command implementations will significantly improve operational safety, however it is possible only when recommendations defined in this article are taken into account. This means that all the components including interfaces have to meet acceptable hazard rate 10E-9 and have to be properly design, constructed, assembled and maintained, all taking into account whole chain of functions performed and supervised by different railway entities.